The Effect of Vocabulary Knowledge on Reading Comprehension to Seventh Grade Students of MTs Miftahul Ulum - Khorida Nur Jannah; Diah Retno Widowati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract:One of the difficulties commonly encountered by students in comprehending reading text is lack of vocabulary mastery. Therefore, the researcher in this study decides to organize research that focuses on the effect of vocabulary knowledge toward students reading comprehension ability. The purpose of this study was to investigate whether the students who experience the vocabulary knowledge treatment achieve better than those who do not experience it. The research design of this study was quantitative quasi- experimental study. While, the population of the study was the seven grade students of MTs Miftahul Ulum. From that population, the samples were 43 students of MTs Miftahul Ulum. The instruments of the research were pretest and posttest questions focusing on descriptive text. The scores of the test were collected and analyzed using IBM SPSS version 24. Wilcoxon test and Mann Whitney test were used to analyze the data. The result of the study shows that students’ score of experimental group is significanly higher than students’ score of control group. Therefore, it can be concluded that vocabulary knowledge is a suitable treatment in helping students to improve their reading comprehension.Keywords: vocabulary knowledge, students, and reading comprehension